COVID-19 impacts and adaptations in Asia and Africa's aquatic food value chains. (July 2021) - Belton, Ben; Rosen, Leah; Middleton, Lucinda; Ghazali, Saadiah; Mamun, Abdullah-Al; Shieh, Jacqueline; Noronha, Hamia S.; Dhar, Goutam; Ilyas, Mohammod; Price, Christopher; Nasr-Allah, Ahmed; Elsira, Ibrahim; et al.
Abstract: The COVID-19 pandemic is a shock affecting all areas of the global food system. We tracked the impacts of COVID-19 and associated policy responses on the availability and price of aquatic foods and production inputs during 2020, using a high frequency longitudinal survey of 768 respondents in Bangladesh, Egypt, India, Myanmar, Nigeria. We found the following: (1) Aquatic food value chains were severely disrupted but most effects on the availability and accessibility of aquatic foods and production inputs were short-lived. (2) Impacts on demand for aquatic foods, production inputs, and labor have been longer lasting than impacts on their supply. (3) Retail prices of aquatic foods spiked briefly during March-May 2020 but trended down thereafter, whereas prices of production inputs rose. These trends suggest a deepening 'squeeze' on the financial viability of producers and other value chain actors. (4) Survey respondents adapted to the challenges of COVID-19 by reducing production costs, sourcing alternative inputs, diversifying business activities, leveraging social capital, borrowing, seeking alternative employment, and reducing food consumption. Many of these coping strategies are likely to undermine well-being and longer-term resilience, but we also find some evidence of proactive strategies with potential to strengthen business performance. Global production of aquatic food likely contracted significantly in 2020. The importance of aquatic food value chains in supporting livelihoods and food and nutrition security in Asia and Africa makes their revitalization essential in the context of COVID-19 recovery efforts. We outline immediate and longer-term policies and interventions to support this goal. Highlights: We track impacts of COVID-19 policies on aquatic food supply chains in Asia and Africa. Short-term impacts on aquatic food and production inputs supply, longer-run impacts on demand. Deepening squeeze on financial viability of producers and other supply chain actors. Actors adapted to challenges with reactive coping strategies and proactive measures. Aquatic food supply chains can play important role in COVID-19 recovery.